Proceedings of the 3rd Workshop on Gender Bias in Natural Language Processing 2021
DOI: 10.18653/v1/2021.gebnlp-1.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Gender Bias in Hindi-English Machine Translation

Abstract: With language models being deployed increasingly in the real world, it is essential to address the issue of the fairness of their outputs. The word embedding representations of these language models often implicitly draw unwanted associations that form a social bias within the model. The nature of gendered languages like Hindi, poses an additional problem to the quantification and mitigation of bias, owing to the change in the form of the words in the sentence, based on the gender of the subject. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Cho et al ( 2019) introduced translation gender bias index (TGBI) as a metric to measure bias in NMT systems using gender-neutral source language sentences, originally for the Korean language. Ramesh et al (2021) showed that the TGBI metric can be applied to Hindi too. They constructed seven sets (P 1 to P 7 ) of gender-neutral sentences in Hindi which included: formal (S1), impolite (S2), informal (S3), occupation (S4), negative (S5), polite (S6), and positive (S7) versions.…”
Section: Tgbi Evaluation Using Gender-neutral Sentencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cho et al ( 2019) introduced translation gender bias index (TGBI) as a metric to measure bias in NMT systems using gender-neutral source language sentences, originally for the Korean language. Ramesh et al (2021) showed that the TGBI metric can be applied to Hindi too. They constructed seven sets (P 1 to P 7 ) of gender-neutral sentences in Hindi which included: formal (S1), impolite (S2), informal (S3), occupation (S4), negative (S5), polite (S6), and positive (S7) versions.…”
Section: Tgbi Evaluation Using Gender-neutral Sentencesmentioning
confidence: 99%
“…This problem also exists for HI-EN Machine Translation (Ramesh et al, 2021). When put to use, such systems can cause various harms (Savoldi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with this method is that it needs a labeled gender dataset beforehand to train the classifier. Recent work by Ramesh et al (2021) tries to find out bias in English-Hindi machine translation. They implement a modified version of the TGBI metric based on grammatical considerations for Hindi.…”
Section: Related Workmentioning
confidence: 99%
“…Cho et al [2019] expect TGBI to be a representative measure for inter-system comparison, especially if the gap between the systems is noticeable. Recently, Ramesh et al [2021] extend TGBI to Hindi. In general, this is a suitable method for applications where male default is the predominant risk.…”
Section: Causal Biasmentioning
confidence: 99%